2019
DOI: 10.1097/icb.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exudative Paraneoplastic Polymorphous Vitelliform Maculopathy During Vemurafenib and Pembrolizumab Treatment for Metastatic Melanoma

Abstract: Purpose To describe a case of a patient with BRAF mutation-positive cutaneous melanoma who developed acute exudative polymorphous vitelliform maculopathy (AEPVM) during vemurafenib and pembrolizumab treatment for metastatic melanoma. Methods Retrospective case report documented with wide-field fundus imaging, spectral domain optical coherence tomography (SD-OCT) and fundus autofluorescence imaging. Results A 55-year-old woman bilateral ductal breast carcinoma and BRAF mutation positive metastatic cutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 9 publications
(26 reference statements)
2
23
0
Order By: Relevance
“…To our knowledge, there were two reports that showed similar OCT findings to those in our case during the course of chemotherapy with immune checkpoint inhibitor for malignant melanoma 9. Recently, Sandhu et al reported a case of paraneoplastic polymorphous vitelliform maculopathy during vemurafenib and pembrolizumab treatment and OCT findings were similar to those in our case 10…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, there were two reports that showed similar OCT findings to those in our case during the course of chemotherapy with immune checkpoint inhibitor for malignant melanoma 9. Recently, Sandhu et al reported a case of paraneoplastic polymorphous vitelliform maculopathy during vemurafenib and pembrolizumab treatment and OCT findings were similar to those in our case 10…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, paraneoplastic AEPVM is thought to be a variant of melanoma-associated retinopathy. There is a recent report describing paraneoplastic AEPVM as closely resembling the course of our case in their patient treated with a combination of vemurafenib (a BRAF inhibitor) and pembrolizumab, which has the same mechanism of action as nivolumab, administered as an anti-PD-1 antibody agent for metastatic melanoma [8]. Discontinuation of vemurafenib and introduction of difluprednate and dorzolamide led to a gradual resolution of AEPVM.…”
Section: Discussionsupporting
confidence: 78%
“…Another possible diagnosis is the paraneoplastic acute exudative polymorphous vitelliform maculopathy (AEPVM) seen in patients with metastatic melanoma [8,9]. AEPVM is a rare disorder associated with multifocal areas of serous detachment and subretinal accumulation of hyperautofluorescent yellowish material in the posterior pole [10].…”
Section: Discussionmentioning
confidence: 99%
“…There can be consideration given to the fact that the patient was formerly on pembrolizumab as well which has been seen to cause inflammatory changes in the eye, 8 and has also been a medication used during another documented case of AEPVM. 9 The authors of this case describe a patient developing AEPVM days after starting vemurafenib, which was subsequently stopped due to ocular symptoms, all the while on pembrolizumab among other forms of therapy. These authors also considered whether pembrolizumab could be a cause of the condition, however the patient had been on this therapy for some time and the condition improved over four months while still on the medication, which should seemingly argue against it being causative.…”
Section: Discussionmentioning
confidence: 99%